Joint Trajectory and Resource Allocation Optimization for Two-Way UAV-aided Relaying Network - Liang, Yipeng; Xiao, Lin; Yang, Dingcheng; Lu, Keju (International Conference on Wireless Communications and Signal Processing, 2020)
In this paper, a UAV-aided two-way relaying net-work based on physical-layer network coding (PNC) protocol is considered, where an unmanned aerial vehicle (UAV) is employed to assist two ground nodes (GNs) to communicate with each other due to the direct link is blocked or too weak to ignore. A novel scheme based on slots pairing is proposed so as to maximize the total rate of the mobile relaying network. The total rate maximization problem is formulated, which subjects to UAV mobility, power allocation, slots pairing as well as time-causality. Since it is a non-convex problem whose global optimal solution is difficult to obtain, an effective iterative algorithm is designed to derive a local solution by adopting the block co-ordinate descent and successive convex optimization techniques. Benchmarks of different relaying schemes are presented to reveal the ascendancy of the proposed scheme. Simulation results show that our proposed design contributes to significant performance enhancement on the total rate of the relaying network compared with other benchmarks.